Elevation variations in volatile components of St. John’s Wort (Hypericum perforatum L.) - Oktay Demir; Ayşegül Tekeş; Sermin Göksu Karagöz; Serkan Gülsoy; Münevver Arslan; Nazlı Öğüt; Şükran Oğuzoğlu (Turkish Journal of Forestry)
In this study, essential oil components of the flowers and leaves of Hypericum perforatum L., from three different elevation groups and 7 sample areas in Sultandağı region of Afyonkarahisar province, were analyzed. Analyzes were carried out using the HS-SPME (Head Space – Solid Phase Micro Extraction) method. As a result, 113 components from flowers and 122 components from leaves were identified. While 72 of the components from flowers are common to all elevation groups, 18 are in a single elevation group. The number of components in flowers is 100 in the lower, 93 in the middle, and 87 in the upper elevation group. 122 components were determined in the leaves. While 73 of these are common to all elevation groups, 18 are in a single. 106 of these components in the leaves were detected in the lower elevation group, 90 in the middle and 103 in the upper. As the altitude increased, the number of components in the flowers decreased. In the leaves, there was no linear increase with altitude. The main components with the highest ratio are -pinene, 5-methyl-undecane and trans-caryophyllene in the flowers, and 2-methyl-octane, carvacrol and acetic acid in the leaves. While it is seen the main components of the essential oils of flowers and leaves are similar in the altitude groups, the alteration is generally in other chemical components. It was concluded this variability in the composition and ratios is significantly dependent on elevation-dependent climatic conditions and the phenological state of the plant shaped by their combination.